2001
DOI: 10.1054/bjoc.2000.1638
|View full text |Cite
|
Sign up to set email alerts
|

Copy number gain at 12q12-14 may be important in the transformation from follicular lymphoma to diffuse large B cell lymphoma

Abstract: The purpose of this study was to identify novel areas of genomic copy number change associated with transformation from follicular lymphoma (FL) to diffuse large B cell lymphoma (DLBL). DNA was extracted from tumour cells micro-dissected from paraffin- embedded tissue sections in 24 patients with FL and subsequent transformation to DLBL and 18 patients with de novo DLBL. Tumour DNA was compared to reference DNA using comparative genomic hybridization. Abnormalities common to all 3 groups were gains on chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 28 publications
5
41
1
Order By: Relevance
“…46,51,52 However, in t-FL disomy may not be the case, with CGH analysis demonstrating gains at 12q12-14 in 50% of t-FL samples. 11 Although this study confirms TP53 mutation as a contributory genetic mechanism in the process of transformation, the variable functional consequences and limited frequency suggests that targeting p53 may have only limited clinical application, instead targeting MDM2 overexpression on transformation may hold the greater promise.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…46,51,52 However, in t-FL disomy may not be the case, with CGH analysis demonstrating gains at 12q12-14 in 50% of t-FL samples. 11 Although this study confirms TP53 mutation as a contributory genetic mechanism in the process of transformation, the variable functional consequences and limited frequency suggests that targeting p53 may have only limited clinical application, instead targeting MDM2 overexpression on transformation may hold the greater promise.…”
Section: Discussionmentioning
confidence: 66%
“…48 Our observations are, however, more consistent with conventional and array-based comparative genomic hybridisation (CGH) studies of sequential FL/t-FL pairs that demonstrate only infrequent loss of 17p upon transformation. 11,13 Thus, the minority of transformation events were associated with the TP53 mutation or LOH. The alternative oncogenic mechanisms that result in phenotypic change as yet remain unclear; their elucidation hampered by limited sample availability for paired analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, copy number gains at the 12q12-14 region, which contains the CDK2 gene, have been widely associated with human Diffuse Large BCell Lymphoma (DLBCL). [49][50][51] Deregulation of NFAT signaling pathway has been associated with different human malignancies, including lymphomas and leukemias. [52][53][54] Sustained activation of Calcineurin has been observed in both human B and T cell lymphomas, and showed intrinsic effects in the proliferation and survival of these cells, highlighting the importance of NFAT transcription factors in these malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification of the 6p21 locus, where cyclin D3 is mapped, has been previously reported by microsatellite analysis and comparative genomic hybridization in up to 7% of FLs. 10,11,13,14 Nevertheless, 6p21 amplification is unlikely to be specific for FL, since it has been also reported in 6% of diffuse large B-cell NHLs, 12 in 13% of primary gastric NHLs 25 and in 30% of NK NHL/leukemias. 26 Using probes specific for the centromeric region and the long arm of the chromosome 6, we found that one case showed a pattern highly suggestive for the presence of an isochromosome 6p.…”
Section: Discussionmentioning
confidence: 99%